2021
DOI: 10.1007/s11356-021-15208-3
|View full text |Cite
|
Sign up to set email alerts
|

A study on the assessment of traffic noise induced annoyance and awareness levels about the potential health effects among residents living around a noise-sensitive area

Abstract: The present cross-sectional study aimed to evaluate the risk factors for traffic noise–induced annoyance and also assess the awareness levels among the exposed population concerning the health impacts caused by traffic noise. Field measurements were made to validate the application of the standard noise models, which were later used to present the acoustical environment and assess the exposure level around a super-speciality hospital surrounded by a residential zone. Results from the noise maps and façade maps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(14 citation statements)
references
References 78 publications
1
11
0
2
Order By: Relevance
“…As for noise, research reporting back noise pollution data to the public is rather scarce [23]. People are often not aware of traffic noise and lack actions to avoid it [53,54]. This is similar to the participants in this study.…”
Section: Empowerment Vs Resignationsupporting
confidence: 71%
“…As for noise, research reporting back noise pollution data to the public is rather scarce [23]. People are often not aware of traffic noise and lack actions to avoid it [53,54]. This is similar to the participants in this study.…”
Section: Empowerment Vs Resignationsupporting
confidence: 71%
“…Research has shown that noise annoyance is more related to road traffic as compared to rail or air traffic [ 34 ]. In a study conducted in Srinagar Municipal Corporation, 565 participants in 41 measurement locations were interviewed with a semi-structured questionnaire that revealed traffic noise was reported by 85% of respondents at home, and approximately 64% of those surveyed considered traffic noise to be extremely loud [ 9 ]. According to the study by Joseph et al, 62.1% of audiologists and 49.1% of the general population believe that hospital staff members are in danger of being impacted by noise at work, which may have negative effects on their ability to focus, regulate their emotions, or perform their jobs efficiently [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies show workers exposed to excessive noise levels are at increased risk for ischemic heart disease (IHD), stroke [ 7 ], hypertension [ 8 ], annoyance, poor sleep quality, and sensitivity to noise [ 9 ] among residents living near highways [ 10 ]. Those with a higher exposure to transportation noise are associated with a higher risk for dementia [ 11 ] and Alzheimer's [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Noise levels such as L10, L90, Ldn, Noise Pollution Level (LNP), Traffic Noise Index (TNI), and Noise Climate (NC) in dB(A) were established to assess the intensity of traffic noise and its effects on the environment (Di et al 2018). Several studies also conducted to analyze the traffic noise induced annoyance level in road side populated areas (Gilani and Mir 2021b). The subjective, behavioral and physiological effects also depends on the energy based acoustic exposure indexes and descriptors (Wunderli et al 2016;Bahadure and Kotharkar 2018;Basner and McGuire 2018).…”
Section: 1 Introductionmentioning
confidence: 99%